Effect of Sevoflurane on Recovery Time in Patients with Surgery in the Operating Room - Christy, Bunga; Burhan, Asmat; Heri Wibowo, Tophan (Global Indonesia Health Care (GOICARE), 2025)
Background: In 2020, 234 million hospital clients made use of health facilities in the globe whereas Indonesia had recorded 1.2 million surgeons (World Health Organization, 2020). Sevoflurane is widely used in surgical procedures and its effect on the duration of recovery time needs further study. Purpose: It aims to conduct research on how sevoflurane affects recovery time among surgical patients at Santa Maria Cilacap General Hospital and will investigate specific objectives which include patient characteristics (age, gender, type of surgery, duration), recovery time post-sevoflurane, and the effect with a 2% MAC sevoflurane. Methods: A one-shot case study pre-experimental design was undertaken with a subject relatively between surgical patients and univariate analysis was conducted to test the distribution of data among all subjects. The number of patients who received a dose of 2% or 3% of sevoflurane were 26 and 30 patients, respectively. Results: Patients mostly fall over 35 years old, even with a higher incidence of females than males. Most patients receive debridement and excision surgery. Recovery times would vary from a surgery that lasts about 30 minutes. Statistical analysis shows normal distribution; meanwhile, the intervention has a significant impact on recovery times. The p-value of the pre-experiment one-shot case study is 0.006, which suggests it is statistically significant (p < 0.05). Conclusion: This study is beneficial to RSU Santa Maria Cilacap in subsequent understanding of the use of sevoflurane in patient care and as an embarking point for further studies on anesthetics and recovery determinants such as comparative studies on inhalation agents